Myocardial ischaemia in a case of a solitary coronary ostium in the right aortic sinus with retroaortic course of the left coronary artery: documentation of the underlying pathophysiological mechanisms of ischaemia by intracoronary Doppler and pressure measurements. Issue 3 (1st September 1998) - Schwarz, E R; Hager, P K; Uebis, R; Hanrath, P; Klues, H G
Abstract : Only a few cases of a single coronary ostium and retroaortic course of the coronary artery have been described. Almost all cases reported so far had additional coronary artery or valvar disease. However, myocardial ischaemia may be caused by the coronary malformation alone. A 40 year old woman with severe myocardial ischaemia in the absence of clinically relevant coronary atherosclerosis is described. To clarify the origin and mechanisms of ischaemia, intracoronary Doppler, pressure and ultrasound studies were performed using microtransducers. In its outer portion along the course behind the ascending aorta, coronary blood flow velocities were increased, there was an external elliptical compression, and distal coronary flow reserve was reduced. Furthermore, an overshoot in diastolic pressure above aortic pressure was detectable within this portion. Dobutamine stimulation exaggerated the observed intracoronary haemodynamics and induced myocardial ischaemia. The intracoronary diagnostic procedures performed were helpful in clarifying the pathophysiological mechanisms of functional coronary obstruction and ischaemia in this malformation. Bypass surgery was successfully performed with symptomatic improvement.